The economics of crude petroleum production - Bradley, Paul G. (Amsterdam : North-Holland Pub. Co., 1967)
The study was undertaken as a doctoral dissertation at the Massachusetts Institute of Technology. Chapter 2 and 3 have been extensively revised since the thesis was presented
Includes bibliographical references: p. [144]-147 and index.
osc 28/01/2019
Loans
Keywords: Petroleum industry and trade